Localization Techniques for Water Pipeline Leakages: A Review - Awang Lah, Airull Azizi; Dziyauddin, Rudzidatul Akmam; MD YUSOFF, NELIDYA (International Journal of Integrated Engineering, 2018)
Pipeline leakages in water distribution network (WDN) is one of the prominent issues that has gain an interest among researchers in the past few years. Time and accuracy play an important role in leak localization as it has huge impact to the human population and economic point of view. The complexity of WDN has prompt numerous techniques and methods been introduced focusing on the accuracy and efficacy. In general, localization techniques can be divided into two broad categories; external and internal systems. This paper reviews some of the techniques that has been explored and proposed including the limitations of each techniques. Â Â